DIFFERENCES IN OSTEOBLAST COUNT AND ITS EFFECT ON ORTHODONTIC MOVEMENT OF DIABETIC MODELS' TEETH AFTER ORAL ADMINISTRATION OF OLIVE OIL - Az-Zahra, Salwa; Handayani, Fani Tuti; Purnama, Ryana Budi; Logamarta, Setiadi W. (Journal of Vocational Health Studies, 2022)
Background: In patients with uncontrolled diabetes, an increase in Advanced glycation end products (AGEs) inhibits osteoblast differentiation so that the number of osteoblasts decreases and interferes with bone formation in orthodontic movement. Giving natural ingredients such as olive oil is proven to increase the number of osteoblasts. Purpose: To determine differences in the number of osteoblasts and their effect on the orthodontic movement of diabetic teeth after oral administration of olive oil. Method: 25 male guinea pigs divided into four groups: diabetic guinea pigs treated with olive oil at a dose of 0.7; 1.05; 1.4 ml/day, distilled water, and healthy guinea pigs were given aquadest. Alveolar bone tissue samples were taken on the 15th day after orthodontic application, and then the number of osteoblasts was calculated histologically. Result: In the diabetic model group treated with olive oil doses of 0.7; 1.05; 1.4 ml/day, distilled water, and healthy guinea pigs given aquades were 2.900 ± 0.678; 4.320 ± 0.497; 5.920 ± 0. 460; 0.200 ± 0.200; 1.320 ± 0.415. The study showed that the olive oil treatment group had more osteoblasts than the untreated group. Analysis one way ANOVA showed a very significant difference between the treatment group and the untreated group (pâ‰¤0.01), while the LSD test showed a significant difference between groups. The highest number of osteoblasts was found at a dose of 1.4 ml/day. Conclusion: There was an increase in osteoblasts in the orthodontic movement of diabetic teeth after oral administration of olive oil.